Co-composting of oil palm frond with palm oil mill effluent - Ahmad, Mohd Najib (2012)
The oil palm biomass namely empty fruit bunches (EFB), oil palm fronds (OPF) and oil palm stems (OPS) are by-products, which are produced about 40 million tons per year, and it has been of great concern recently due to the significant impact on the environment. In the normal practice, the conventional method of OPS and OPF disposal for replanting the oil palm through burning technique at the plantation can cause the problems of air pollution. Composting has been considered as one of the alternative methods to convert organic wastes into beneficial products that benefit plant growth and soil amendment. Therefore, this study was conducted to investigate the physicochemical changes and microbial community during co-composting of oil palm frond and POME anaerobic sludge. The study was carried out at Faculty of Biotechnology and Molecular Science, UPM at a pilot scale with capacity of 1 tonne of oil palm fronds. The ratio of POME anaerobic sludge added onto OPF throughout the composting treatment was one to one. Two batches of composting process were carried out using different structure of oil palm frond (OPF) as compost substrate, namely chipped and chipped-ground oil palm fronds. Results showed that co-composting of OPF and POME anaerobic sludge completed within 60 days with average Carbon/Nitrogen (C/N) ratio of 20. The final or matured compost was grayish in color, having a texture and earthy smell close to that of natural soil. Furthermore, composting of chipped-ground OPF gave better performance with high thermophilic temperature at 56oC and maintained for 35 days, while composting of chipped OPF resulted in 52oC, lasting for only 7 days. The oxygen level and moisture content of the chipped-ground compost was maintained at 2.0-12.0% and 60-70%, respectively, while the chipped compost were 18-20% and 55-60%, respectively. The pH for both composting processes was maintained at 7-8 (alkaline condition). The total bacteria count observed in composting of chipped-ground OPF and chipped OPF were 13x1010 cfu/g and 55x1010 cfu/g at 0 day and decreased to 0.5x1010 cfu/g and 3.7x1010 cfu/g at 60 DOC, respectively. The carbon to nitrogen ratio observed in composting of chipped ground OPF and chipped OPF was 64 and 80 at 0 day and decreased until 18 and 20 at 60 days of composting, respectively. The final cured compost for both composting processes contained a considerable amount of nutrients and trace elements. The heavy metal contents such as Cr, Cd, Pb and Ni in the final compost were low and within US EPA level, < 20 mg kg-1. The diversity of the bacterial community investigated using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE)indicated that the composting processes of chipped and chipped - ground OPF with POME anaerobic sludge was dominated by Pseudomonas sp. species.